Primerjava motivacije in poteka pouka pri poučevanju francoščine otrok in odraslih - Paternost, Katarina (Vestnik za tuje jezike, 2013)
Motivation of pupils and the question of how to motivate them seems to be the main issue of language teachers. As a French language teacher of both, children and adults, I have acquired quite some experiences in the past seven years of teaching in different language schools. These experiences are a great help in preparing my courses. However, as there is no established curricula in the language schools, which is quite a difference in comparison to public elementary and high schools, every teacher is expected to create his or her particular curriculum. This means literature, topics and matters that course will cover have to be selected by the teacher, and the teacher prepares all the handouts. If the level of satisfaction differs from the expectations of the pupils, they will most likely refuse to participate in the future. Because of that the question of motivation remains one of the main issues in terms of language teaching. The aim of the article is the comparison of the methods of raising motivation among the pupils I teach in two different language schools. The first group is mainly focused on children and the second group is focused on adults.
Keywords: francoščina; French; tuji jeziki; jezikovni pouk; motivacija; motivation